2011
DOI: 10.1002/ca.21201
|View full text |Cite
|
Sign up to set email alerts
|

Nerve terminal distribution in the human tongue intrinsic muscles: An immunohistochemical study using midterm fetuses

Abstract: Desmin and vimentin are intermediate filaments that play crucial roles in maturation, maintenance and recovery of muscle fibers and mesenchymal cells. The expression of these proteins has not been investigated extensively in human fetuses. In the present study, we examined the immunohistochemical expression of intermediate filaments in skeletal muscles of the head, neck and thorax in 12 mid-term human fetuses at 9-18 weeks of gestation. We also used immunohistochemistry to localise expression of the myosin hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The nerve density was highest in the CPM. No such cluster of nerves, or plexus, is seen in the fetal tongue at the same stage [11]. We confirmed the curved or recurrent courses of the pharyngeal nerves that had been previously described by Shimokawa et al [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The nerve density was highest in the CPM. No such cluster of nerves, or plexus, is seen in the fetal tongue at the same stage [11]. We confirmed the curved or recurrent courses of the pharyngeal nerves that had been previously described by Shimokawa et al [6].…”
Section: Discussionsupporting
confidence: 90%
“…However, in these high-magnification photos, it was difficult to identify the topographical anatomy of the nerve courses. Our recent immunohistochemical study using human fetuses [11] revealed that the pharyngeal muscles are so large at 20-25 weeks of gestation, that the nerves supplying them are clearly identifiable at lower magnifications. Moreover, the fetal upper pharyngeal muscles provide a thick muscle mass, in contrast to the thin, lower pharyngeal wall.…”
Section: Introductionmentioning
confidence: 99%
“…This difference occurred in the level above the squamous‐columnar epithelial junction, that is, the lower part of Figure . The typical end‐plate band for striated muscle innervation (Abe et al, ) was seen in the external anal sphincter in three of the 12 cadavers (Fig. B).…”
Section: Resultsmentioning
confidence: 78%
“…All these figures are for a 9-week fetus. But beginning at 15 weeks, the linear terminal in the semispinalis muscle developed into a thicker structure, recently termed the 'endplate band' by Mu & Sanders (2010) and Abe et al (2011) (not shown). We attempted to trace the segmental nerve in semiserial sections based on S100 immunostaining, but we were not able to identify a single multifidus muscle bundle innervated by two segmental nerves.…”
Section: Resultsmentioning
confidence: 99%
“…For each fetus, 50-200 sections were obtained, depending on fetus size. Most sections were stained with hematoxylin and eosin (HE), but some sections (four sections for every 10 sections) underwent immunohistochemical staining for (i) peripheral nerves (S100 protein; Niikura et al 2010;Abe et al 2011), (ii) striated muscle fibers (desmin; Abe et al 2010), (iii) vessels and stromal mesenchyme (CD34; Katori et al 2011a), and (iv) macrophages (CD68; Kim et al 2011). All studies cited for immunostaining applications were recently performed by our group using human fetuses.…”
Section: A B Cmentioning
confidence: 99%